Penerapan Building Maintenance sebagai Upaya Optimalisasi Fungsi Gedung Studi Kasus: Rusun Jagakarsa Jakarta Selatan - Dewanti, Rizci Purna; Mahardika, Daffa; Windari, Aulia Choiri (Universitas Muhammadiyah Palembang, 2025)
Building maintenance is a crucial aspect of a building’s life cycle to ensure its functionality, comfort, and safety for occupants. This study aims to analyze the implementation of building maintenance at Jagakarsa Flats, South Jakarta, as an effort to optimize building performance. The research employed a case study method with a descriptive qualitative approach through online interviews and analysis of the Work Plan and Requirements (RKS), Terms of Reference (KAK), and relevant technical regulations. The findings show that maintenance activities for the mechanical, electrical, plumbing, and civil aspects have been carried out in accordance with the RKS, while housekeeping and exterior space aspects have not been fully documented. A gap was also found between field practices and national standards (Minister of Public Works Regulation No. 24/PRT/M/2008), particularly regarding inspection frequency and documentation. In conclusion, the implementation of building maintenance at Jagakarsa Flats is generally effective but requires stronger preventive maintenance strategies and more systematic documentation to ensure sustainable building functionality. This research contributes to improving building maintenance management practices in vertical housing within urban areas.